2023
DOI: 10.1108/jhti-08-2022-0356
|View full text |Cite
|
Sign up to set email alerts
|

Vacation vengeance: an interpretive phenomenological analysis of revenge travel in India

Abstract: PurposeAfter each of the COVID-19-induced lockdowns, an unprecedented surge in leisure travel was observed, resulting in tourists flocking to places of tourist interest. This phenomenon was termed revenge travel in popular literature. The purpose of this study is to explore the phenomenon of revenge travel in detail through an academic lens. It examines the psychological and emotional motivations for revenge travel while studying the differences in travel behaviour pre- and post-pandemic.Design/methodology/app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Prior scholars have also used a similar approach for reporting their studies (e.g. see Romaniuk et al , 2022; Singh and Srivastava, 2023). Booth et al (2014) have suggested that COREQ favors a more realistic and pragmatic paradigm for reporting qualitative findings.…”
Section: Methodsmentioning
confidence: 99%
“…Prior scholars have also used a similar approach for reporting their studies (e.g. see Romaniuk et al , 2022; Singh and Srivastava, 2023). Booth et al (2014) have suggested that COREQ favors a more realistic and pragmatic paradigm for reporting qualitative findings.…”
Section: Methodsmentioning
confidence: 99%
“…Following the relaxation of restrictions, a noteworthy phenomenon known as "Revenge Tourism" has surfaced [7] . This term refers to the behavior of individuals who, after enduring prolonged periods of confinement, engage in travel activities with a heightened sense of enthusiasm [8,9] . The increase in travel, particularly in areas such as Banyumas Regency, has been intensified by the deliberate utilization of social media platforms, which have a significant impact on shaping perspectives and impacting travel choices [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, there are a small number of researchers who feel IPA is suited for tourism research, e.g. Farkic, 2020;Rickly, 2022;Sedgley et al, 2017;Singh & Srivastava, 2023;Thomas & Nieuwerburgh, 2022. To fulfil my thesis's, aim of gaining an experiential understanding of disabled people using VR to access adventure tourism, my research takes a phenomenological standpoint. To gain the level of insight needed, I use IPA as a theoretical framework and methodology to explore the lived experiences of twelve disabled people based in South Wales, UK.…”
Section: Aim and Objectives Of Thesismentioning
confidence: 99%
“…Some researchers suggest that they are using phenomenology without acknowledging the theoretical tenets, or which phenomenology type is being applied methodically (e.g., Cohen, 1979;Marschall, 2015;Masberg & Silverman, 1996). There is confusion between types of phenomenology and the phenomenological tenets, such as bracketing, a tenet aligned with descriptive phenomenology being used for interpretative phenomenology (e.g., Laing & Frost, 2017;Singh & Srivastava, 2023). Specifically, Hayllar & Griffin (2005) and Berdychevsky & Gibson (2015) state they are using descriptive phenomenology, whilst applying interpretative phenomenological tenets and methods.…”
Section: Phenomenology and Ipa In Tourism Researchmentioning
confidence: 99%
See 1 more Smart Citation